Editorial - Gough, Melinda J.; Kelly, Erin E. (Early Theatre)

(untitled) (McMaster University Library Press / Becker Associates, 2023)
This editorial launches our open call for book reviews editor(s), announces our 2023 essay prize winners, and commemorates the life of our late colleague and editorial board member Dr JoAnna Dutka.